NADPH Oxidases in Diastolic Dysfunction and Heart Failure with Preserved Ejection Fraction - James P. Teuber; Kobina Essandoh; Scott L. Hummel; Nageswara R. Madamanchi; Matthew J. Brody (MDPI AG, 2022)
Nicotinamide adenine dinucleotide phosphate (NADPH) oxidases regulate production of reactive oxygen species (ROS) that cause oxidative damage to cellular components but also regulate redox signaling in many cell types with essential functions in the cardiovascular system. Research over the past couple of decades has uncovered mechanisms by which NADPH oxidase (NOX) enzymes regulate oxidative stress and compartmentalize intracellular signaling in endothelial cells, smooth muscle cells, macrophages, cardiomyocytes, fibroblasts, and other cell types. NOX2 and NOX4, for example, regulate distinct redox signaling mechanisms in cardiac myocytes pertinent to the onset and progression of cardiac hypertrophy and heart failure. Heart failure with preserved ejection fraction (HFpEF), which accounts for at least half of all heart failure cases and has few effective treatments to date, is classically associated with ventricular diastolic dysfunction, i.e., defects in ventricular relaxation and/or filling. However, HFpEF afflicts multiple organ systems and is associated with systemic pathologies including inflammation, oxidative stress, arterial stiffening, cardiac fibrosis, and renal, adipose tissue, and skeletal muscle dysfunction. Basic science studies and clinical data suggest a role for systemic and myocardial oxidative stress in HFpEF, and evidence from animal models demonstrates the critical functions of NOX enzymes in diastolic function and several HFpEF-associated comorbidities. Here, we discuss the roles of NOX enzymes in cardiovascular cells that are pertinent to the development and progression of diastolic dysfunction and HFpEF and outline potential clinical implications.